Malecón en la ribera del Río Magdalena Girardot (2021)
According to the disposition of the Girardot development plan with respect to the distribution of the treatments implemented for the city, it is specified that commune 2 is undergoing renovation treatment, due to the state of deterioration in which it is not counting with proper urban planning; For this reason, it is important to analyze the evolution of the sector in relation to the Magdalena River, since the construction of urban spaces integrating the surrounding heritage elements leads to the generation of economic and socio-cultural growth.